Architectural characteristics and determination of load-bearing capacity as a key indicator for a strengthening of the primary school buildings: Case study Osijek. (December 2021) - Hadzima-Nyarko, Marijana; Ademović, Naida; Krajnović, Marija
Abstract: Safety is one of the most important characteristics of a school building. The major role of school space in the children's growth encouraged architects, engineers, and scientists to analyze existing school buildings construction systems and possibilities for their strengthening. The estimation of earthquake structural damage is a very useful tool in reducing the impact of earthquake effects on material and social elements. This is extremely important for schools so that those with insufficient seismic resistance can be strengthened and thus prevent collapse in the event of a sudden earthquake. In this paper, the architectural and structural characteristics of the existing primary school buildings in Osijek (Croatia) will be analyzed in order to perform an estimation of earthquake structural damage on the example of a selected school building reinforced concrete (RC) frame. A detailed description of primary school buildings development shows that RC frame was the most common type of school building construction system in the city of Osijek. The review and analysis of each building can become a study or manual for a quality renovation. The approach to their renovation, extension, and reconstruction must be well studied, scientifically based, and have clear goals that will satisfy all users of the school building.